Analisis Informasi Laporan Arus Kas Sebagai Alat Ukur Efektivitas Kinerja Keuangan Pada Pt Lionmesh Prima Jakarta Tbk Tahun 2012-2017 - Hasiatul Aini; Rahma Julita (Jurnal Akuntansi dan Keuangan, 2018)
The  purpose of this research is to the potential for effectiveness of financial performance at PT Lionmeh Prima Jakarta Tbk . The data used are financial statements of PT Lionmesh Prima listed in Indonesia stock exchange 2012-2017 periode. The analytical method used in this research is ratio analysis of cash flow statements.The results of this study explain that: PT Lionmesh Prima Jakarta Tbk for a period of 6 years (2012-2017) which is seen from the ratio of cash flow statement analysis shows less effective results, where the ratio of operating cash flows obtained under 1 (one) and several ratios shows the results has not been reached maximally and fluctuates every year and there is a ratio that shows negative results.The  purpose of this research is to the potential for effectiveness of financial performance at PT Lionmeh Prima Jakarta Tbk . The data used are financial statements of PT Lionmesh Prima listed in Indonesia stock exchange 2012-2017 periode. The analytical method used in this research is ratio analysis of cash flow statements.The results of this study explain that: PT Lionmesh Prima Jakarta Tbk for a period of 6 years (2012-2017) which is seen from the ratio of cash flow statement analysis shows less effective results, where the ratio of operating cash flows obtained under 1 (one) and several ratios shows the results has not been reached maximally and fluctuates every year and there is a ratio that shows negative results.